EEE Assist : an e-portal that encourages mentorship in EEE - Wee, Eunice Ying Ying (Nanyang Technological University, 2020)
This project aims to create an E-portal where students are allowed to connect with mentor and build a long-lasting relationship in the process. EEEAssist is built based on the agile model which allows feedbacks and changes can be made to it based on the feedbacks. It is done in a local environment using XAMPP, using MySQL as the choice of database. Multiple computing languages are used in the creating of webpages such as HTML, CSS, JavaScript, and PHP. The final product allows users to connect with their desired mentors from a database which will be displayed on the webpage. Questions and answers can also be posted for users to answer and clear their queries on academic life. It hopes that through this project, a vibrant community can be built in EEE.